Facial nerve motor-evoked potential monitoring during skull base surgery predicts facial nerve outcome. Issue 9 (1st February 2008) - Fukuda, M; Oishi, M; Takao, T; Saito, A; Fujii, Y
Abstract : Objective: To determine whether monitoring facial nerve motor-evoked potentials (FNMEPs) elicited by transcranial electrical stimulation during skull base tumour surgery is useful for predicting facial nerve outcome. Methods: This study analysed FNMEP findings in 26 patients with skull base tumours. Corkscrew electrodes positioned at C3 or C4 and Cz were used to deliver supramaximal stimuli (180–550 V). FNMEPs were recorded from the orbicularis oculi and oris muscles. The correlation between the final-to-baseline FNMEP ratio and postoperative facial nerve function was examined. Results: Postoperative facial nerve function correlated significantly with the FNMEP ratios in the orbicularis oculi (p = 0.004) and orbicularis oris (p<0.001) muscles. An FNMEP ratio of <50% consistently predicted immediate postoperative facial palsy, although the degree of palsy differed among patients. All patients had satisfactory facial nerve function (House and Brackmann grades I and II) postoperatively if the FNMEP ratio remained at >50%. Conclusions: Intraoperative FNMEP monitoring can be useful for predicting facial nerve function after skull base surgery. This new method is a valuable adjunct to conventional facial nerve monitoring.